2006
DOI: 10.1080/00224490609552308
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between negative mood and sexuality in heterosexual college women and men

Abstract: Negative mood states, such as depression and anxiety, are typically associated with decreased sexual interest and arousal. However, there is also some evidence that depressed or anxious mood may increase sexual interest or arousal in some individuals. In this study, 663 female college students (mean age = 18.9 years, SD = 1.21) answered questions regarding the effects of anxious and depressed mood on sexual interest and arousal and completed trait measures of sexual excitation and inhibition, anxiety, and depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
82
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 28 publications
20
82
2
4
Order By: Relevance
“…Studies have shown that poorer sexual functioning is associated with greater negative mood states including anxiety and depression (Lykins, Janssen, & Graham, 2006), as well as greater partner conflict (Dennerstein, Lehert, Burger, & Dudley, 1999). In sum, each sexual experience is affected by physical, relational, and psychological factors and daily experience measures are better able to capture changes in sexual function across these events.…”
Section: Assessing Daily Sexual Function In Womenmentioning
confidence: 99%
“…Studies have shown that poorer sexual functioning is associated with greater negative mood states including anxiety and depression (Lykins, Janssen, & Graham, 2006), as well as greater partner conflict (Dennerstein, Lehert, Burger, & Dudley, 1999). In sum, each sexual experience is affected by physical, relational, and psychological factors and daily experience measures are better able to capture changes in sexual function across these events.…”
Section: Assessing Daily Sexual Function In Womenmentioning
confidence: 99%
“…In recent years, a body of research based on the Dual Control Model has emerged, including studies using the SIS/SES and studies using the SESII-W. Research has linked propensity for sexual inhibition and sexual excitation to sexual risk-taking , the experience of sexual problems Sanders et al, 2008), sexual orientation (Bancroft, Carnes, Janssen, & Long, 2005;Sanders at el., 2008), and mood (Bancroft, Janssen, Strong, Vukadinovic, & Long, 2003;Lykins, Janssen, & Graham, 2006). The SESII-W/M includes a broad range of factors which can inhibit or enhance sexual arousal, factors which other research has shown to be relevant for both women and men (Graham et al, 2004;Janssen et al, 2008).…”
mentioning
confidence: 99%
“…Contudo, outros autores referem que existem indivíduos com ansiedade elevada e que não experienciam esta diminuição da libido, sugerindo que a experiencia subjetiva deste estado afectivo negativo pode ser reduzida pelo envolvimento no comportamento sexual (Bancroft et al, 2004). Neste contexto, os indivíduos podem-se envolver em atividade sexual por razões de auto-valorização, intimidade e como forma de regular e melhorar o humor (Lykins, Janssen, & Graham, 2006). Existe evidência de que os comportamentos sexuais de risco aumentam com a ansiedade (Bancroft et al, 2004).…”
Section: Ansiedade E Comportamentos Sexuais De Riscounclassified